Oligometastatic disease in prostate cancer, a continuously changing paradigm: patient selection and treatment strategy - Fodor, Andrei; Cozzarini, Cesare; Fiorino, Claudio; Di Muzio, Nadia Gisella (Translational Cancer Research, 2017)
The recent publication of the results of a relatively large cohort of patients treated with stereotactic body radiation therapy (SBRT) at the Mayo Clinic for oligometastatic prostate cancer (1) has to be considered as another significant step toward the assessment of the potential of radiation therapy in the optimal management of these “niche” patients.